Fictive Scratching Patterns in Brain Cortex-Ablated, Midcollicular Decerebrate, and Spinal Cats - Aguilar Garcia, Irene Guadalupe; Dueñas-Jiménez, Judith Marcela; Castillo, Luis; Osuna-Carrasco, Laura Paulina; De La Torre Valdovinos, Braniff; Castañeda-Arellano, Rolando; López-Ruiz, Jose Roberto; Toro-Castillo, Carmen; Treviño, Mario; Mendizabal-Ruiz, Gerardo; Duenas-Jimenez, Sergio Horacio (Frontiers in Neural Circuits, 2020)
Background: The spinal cord’s central pattern generators (CPGs) have been explained by the symmetrical half-center hypothesis, the bursts generator, computational models, and more recently by connectome circuits. Asymmetrical models, at odds with the half-center paradigm, are composed of extensor and flexor CPG modules. Other models include not only flexor and extensor motoneurons but also motoneuron pools controlling biarticular muscles. It is unknown whether a preferred model can explain some particularities that fictive scratching (FS) in the cat presents. The first aim of this study was to investigate FS patterns considering the aiming and the rhythmic periods, and second, to examine the effects of serotonin (5HT) on and segmental inputs to FS. Methods: The experiments were carried out first in brain cortex-ablated cats (BCAC), then spinalized (SC), and for the midcollicular (MCC) preparation. Subjects were immobilized and the peripheral nerves were used to elicit the Monosynaptic reflex (MR), to modify the scratching patterns and for electroneurogram recordings. Results: In BCAC, FS was produced by pinna stimulation and, in some cases, by serotonin. The scratching aiming phase (AP) initiates with the activation of either flexor or extensor motoneurons. Serotonin application during the AP produced simultaneous extensor and flexor bursts. Furthermore, WAY 100635 (5HT1A antagonist) produced a brief burst in the tibialis anterior (TA) nerve, followed by a reduction in its electroneurogram (ENG), while the soleus ENG remained silent. In SC, rhythmic phase (RP) activity was recorded in the soleus motoneurons. Serotonin or WAY produced FS bouts. The electrical stimulation of Ia afferent fibers produced heteronymous MRes waxing and waning during the scratch cycle. In MCC, FS began with flexor activity. Electrical stimulation of either deep peroneus (DP) or superficial peroneus (SP) nerves increased the duration of the TA electroneurogram. Medial gastrocnemius (MG) stretching or MG nerve electrical stimulation produced a reduction in the TA electroneurogram and an initial MG extensor burst. MRes waxed and waned during the scratch cycle. Conclusion: Descending pathways and segmental afferent fibers, as well as 5-HT and WAY, can change the FS pattern. To our understanding, the half-center hypothesis is the most suitable for explaining the AP in MCC.